Atypical interference effect of action observation in autism spectrum conditions. Issue 4 (March 2014) - Cook, J.; Swapp, D.; Pan, X.; Bianchi-Berthouze, N.; Blakemore, S-J.
<x content-type="archive" xml:space="preserve">Abstract</x> Background Observing incongruent actions interferes with ongoing action execution. This 'interference effect' is larger for observed biological actions than for non-biological actions. The current study used virtual reality to investigate the biological specificity of interference effects of action observation in autism spectrum conditions (ASC). Method High-functioning adults with ASC and age- and IQ-matched healthy controls performed horizontal sinusoidal arm movements whilst observing arm movements conducted by a virtual reality agent with either human or robot form, which moved with either biological motion or at a constant velocity. In another condition, participants made the same arm movements while observing a real human. Observed arm movements were either congruent or incongruent with executed arm movements. An interference effect was calculated as the average variance in the incongruent action dimension during observation of incongruent compared with congruent movements. Results Control participants exhibited an interference effect when observing real human and virtual human agent incongruent movements but not when observing virtual robot agent movements. Individuals with ASC differed from controls in that they showed no interference effects for real human, virtual human or virtual robot movements. Conclusions The current study demonstrates atypical interference effects in ASC.